ANALISIS PENGGUNAAN VIDIO PEMBELAJARAN MATHMAGIC MATERI PECAHAN DI SDN TELANG 2 (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Abstract This research is a type of qualitative descriptive research with an analysis of the use of the Mathmagic learning video for fraction material at SDN Telang 2. This study aims to analyze the use of the Mathmagic learning video for fraction material in class V SDN Telang 2, Kamal District, Bangkalan Regency. The participants in this study were the fifth grade teacher and 11 female students and 8 male students with a total of 19 students. Data collection techniques used by researchers are observation, interviews, questionnaires. The instruments used by the researchers were observation sheets, interviews and student questionnaires. The results of the study show that the use of mathmagic video learning media for fractional material provides students' understanding and interest during learning with 2 indicators of concern. The first indicator is attention (Attention) as many as 16 students or 84% pay attention to the learning videos that are broadcast. This shows that students are more focused on learning when using mathmagic learning videos. The second indicator is satisfaction (Satisfaction) as many as 15 students or 79% pay attention to the learning videos that are broadcast. This shows that students are satisfied with the explanations in the learning videos presented. Keywords: Learning video, Mathmagic, Fractions